Solution-processed lithium-doped ZnO electron transport layer for efficient triple cation (Rb, MA, FA) perovskite solar cells - Mahmud, M.; Elumalai, Naveen Kumar; Upama, M.; Wang, D.; Soufiani, A.; Wright, M.; Xu, C.; Haque, F.; Uddin, A. (American Chemical Society, 2017)
The current work reports the lithium (Li) doping of a low-temperature processed zinc oxide (ZnO) electron transport layer (ETL) for highly efficient, triple-cation-based MA0.57FA0.38Rb0.05PbI3 (MA: methylammonium, FA: formamidinium, Rb: rubidium) perovskite solar cells (PSCs). Lithium intercalation in the host ZnO lattice structure is dominated by interstitial doping phenomena, which passivates the intrinsic defects in ZnO film. In addition, interstitial Li doping also downshifts the Fermi energy position of Li-doped ETL by 30 meV, which contributes to the reduction of the electron injection barrier from the photoactive perovskite layer. Compared to the pristine ZnO, the power conversion efficiency (PCE) of the PSCs incorporating lithium-doped ZnO (Li-doped) is raised from 14.07 to 16.14%. The superior performance is attributed to the reduced current leakage, enhanced charge extraction characteristics, and mitigated trap-assisted recombination phenomena in Li-doped devices, thoroughly investigated by means of electrochemical impedance spectroscopy (EIS) analysis. Li-doped PSCs also exhibit lower photocurrent hysteresis than ZnO devices, which is investigated with regard to the electrode polarization phenomena of the fabricated devices.